Review of researches on mathematical problems of mechanics and control theory at Institute of Mathematics NAS of Ukraine - Lukovsky, I. A.; Mazko, A. G.; Timokha, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
We present a review of researches on mathematical problems of mechanics and control theory conducted at Institute of Mathematics NAS of Ukraine from the beginning of its foundation.